Assessment of pharmacognostic specification of Cannabis sativa leaves in Thailand - Kanittha Nakkliang; Chitlada Areesantichai; Kanchana Rungsihirunrat (Wolters Kluwer Medknow Publications, 2022)
Lack of quality control can affect the safety, efficacy, and acceptability of herbal products that may lead to health problems. Cannabis sativa L. (Cannabaceae) has been widely used as an ethnomedicinal practice for its medicinal values. This study aims to establish pharmacognostic specifications of C. sativa as per standard procedures. Macroscopic-microscopic characteristics, physicochemical parameters, thin-layer chromatography (TLC) fingerprinting, and phytochemical screening of C. sativa leaves collected from various locations throughout Thailand were investigated. Leaves are palmate consists of seven leaflets with green color, margin is serrate with acuminate apex. Anomocytic stomata were found in the upper epidermis while unicellular and glandular trichomes with cystolith were found in the lower epidermis and the epidermis layer covered with cuticle. The physicochemical analysis revealed that the loss on drying (4.068 ± 0.084 %w/w) was within acceptable limits, total ash (14.360 ± 0.084%w/w), acid insoluble ash (2.726 ± 0.080%w/w), ethanol-soluble extractive (11.101 ± 0.223%w/w), water-soluble extractive (23.038 ± 0.306%w/w), and water content (7.523 ± 0.524%w/w). TLC fingerprint showed nine spots with Rf value 0.14, 019, 0.23, 0.29, 0.32, 0.45, 0.58, 0.70, and 0.76. Phytochemical screening of Cannabis leaves indicated the presence of phenolic compounds, flavonoids, alkaloids, diterpenes, triterpenes, and steroids. This study provided referential data for the accurate plant identity, and establishment of cannabis leaves monograph in Thailand.